Penerapan Endorphn Massage Dalam Upaya Menurunkan Tingkat Kecemasan Pada Ibu Bersalin Kala I Di Wilayah Kerja UPTD Puskesmas Toapaya - Fitriany Suangga; Mira Agusthia; Siska Natalia; Wulan Pramadhani; Sri Kurniati (PT. ALHAFI BERKAH INDONESIA, 2023)
Labour is a natural process experienced by mothers giving birth. Pregnant women, mothers giving birth, and postpartum women are groups that are prone to experiencing anxiety. The mother who those feeling anxious during labor stage can giving effect on the process of labor, which is reducing uteri contractility. Various methods than can be used to help reduce anxiety. One of the with Endorphin Massage. Endorphins are known as substances that have many benefits. Some of them are regulating the production of growth and sex hormones, controlling pain and persistent pain, controlling feelings of stress, and boosting the immune system. The emergence of endorphins in the body can be triggered through various activities, such as deep breathing and relaxation, and meditation. Since it is produced by the human body itself, endorphins are considered the best painkillers. Endorphin massage should be done for pregnant women whose gestational age has entered 36 weeks, because at this age the endorphin massage can stimulate the release of the hormone oxytocin which can trigger the birth process.The purpose of this program for the first stage Labour mother in Toapaya Health Center Working Area whose experience anxiety during labour stage ,so that through this program, it can be reduced their anxiety. The impmentation method was carried out by providing endophin message directly to the labour mother